2009
DOI: 10.1120/jacmp.v10i2.2928
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and clinical evaluation of a novel IMRT quality assurance system

Abstract: Intensity‐modulated radiation therapy (IMRT) is a complex procedure that involves the delivery of complex intensity patterns from various gantry angles. Due to the complexity of the treatment plans, the standard care is to perform measurement‐based, patient‐specific quality assurance (QA). IMRT QA is traditionally done with film for relative dose in a plane and with an ion chamber for absolute dose. This is a laborious and time‐consuming process. In this work, we characterized, commissioned, and evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 36 publications
(39 reference statements)
2
73
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In the study 'characterization of the response of the seven29 2D array detector' 11 by Syam et al, the detector's directional dependence was measured as a function of the beam angles and verified by delivering an open field. In the present study, we clinically investigated the angular dependence of a 2D ion-chamber array for IMRT dose verification and quantified the influence of the directional dependence on the effectiveness of the treatment with different IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In the study 'characterization of the response of the seven29 2D array detector' 11 by Syam et al, the detector's directional dependence was measured as a function of the beam angles and verified by delivering an open field. In the present study, we clinically investigated the angular dependence of a 2D ion-chamber array for IMRT dose verification and quantified the influence of the directional dependence on the effectiveness of the treatment with different IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the fluence profile along the moving direction of a leaf pair is created by sweeping the leaf pair with different openings over the field while the beam is always on. [1][2][3][4][5][6][7] IMRT is a complicated procedure that involves the delivery of complex intensity patterns from various gantry angles. Owing to the complexity of the treatment plans, IMRT requires their dosimetric verification, as it produces a steep gradient inside tumors.…”
Section: Introductionmentioning
confidence: 99%
“…8 Many types of dosimeters have been used for patientspecific quality assurance (QA), such as ion chamber, film, 9,10 2-dimensional (2D) diode or ion chamber matrix detectors, [10][11][12][13][14] electronic portal imaging devices, 15 gel dosimetry, 16 and 3D diode arrays. 17,18 3D diode arrays are easy to use and provide 3D dose distributions and QA results, while measurements are being performed. Published studies provide evidence that 3D diode journal homepage: www.meddos.org arrays are accurate and reliable tools for dose verification of VMAT treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These have been verified by many researchers, and these dose evaluation methods are still in use today. 11,[27][28][29][30][31][32][33][34] In addition, the evaluation of an absolute isocenter dose and 2D dose distribution are considered to be adequate for delivery QA of arc therapy, such as IMAT or VMAT. 35,36 Wagner and Vorwerk 35 reported that the use of a 2D ionization chamber (MatriXX™; IBA Dosimetry GmbH, Schwarzenbruck, Germany) for VMAT plan verification is reasonable in clinical routine use.…”
Section: Discussionmentioning
confidence: 99%